Occurrence, diagnosis and management of hepatic fibrosis and cirrhosis: An updated literature review - Jing Qiao (Archives of Hepatitis Research - Peertechz Publications, 2019)
Background: Hepatic fibrosis and cirrhosis, characterized with signifi cant morbidity and mortality, have always been worldwide health care problems. Objective: This manuscript is aimed at providing a research progress overview of hepatic fibrosis and cirrhosis.